First experiences with the Radial Reload with Tri-staple™ technology in low rectal surgery. (February 2015) - van Vugt, Jeroen L.A.; Tegels, Juul J.W.; Derikx, Joep P.M.; Visschers, Ruben G.J.; Stoot, Jan H.M.B.
Abstract: Introduction: Low rectal surgery remains challenging. New surgical stapler devices have been developed to counteract problems of impaired visibility and inability to get low into the pelvis. One of them is the Radial Reload (RR) with Tri-staple ™ Technology (Covidien, New Haven, CT, USA). The aim of this study was to assess the first impressions and experiences regarding handling of this new stapler device in low anterior resection procedures in living humans. Methods: A questionnaire, consisting of 27 statements concerning accessibility, maneuverability and visibility, was sent to 35 surgeons worldwide. Results: A total of 85 rectal surgical procedures, both open and laparoscopic, were assessed by 31 surgeons. In 97% of the procedures the surgeons agreed that the RR stapler device facilitated access in the low pelvis. The first stapler device firing achieved complete transection in 54% of the procedures. According to the surgeons' assessments, in 91% percent of the procedures the RR stapler device enabled creation of adequate margins. Visualization of the pelvic floor was reported in 93% of the procedures. In the surgeons' opinion, the RR stapler device was considered clinically acceptable in 93% of the procedures. In 79% of the procedures the surgeon preferred the RR stapler device over the stapler device they normally used. Conclusion: This study showed that the first experiences with the RR stapler device of 33 surgeons in 85 low rectal procedures are positive. It facilitates low stapling in both open and laparoscopic procedures. Good visibility, maneuverability and the possibility to create adequate distal margins were reported. Highlights: Low rectal surgical procedures remain challenging. Recently, the Endo GIA™ Radial Reload with Tri-staple™ technology was introduced. This study reports surgeons' first experiences using this device in living humans. Good visibility, maneuverability and accessibility of the low pelvis were reported. It was considered clinically acceptable for both open and laparoscopic procedures.